Evaluasi Praktek Kerja Industri Dalam Rangka Meningkatkan Penyerapan Tenaga Kerja Di Dunia Usaha Dan Dunia Industri Di SMK Negeri 2 Lubuklinggau - Belly (Manajer Pendididikan, 2023)
- This study aims in general to evaluate the suitability of the implementation of Industrial Work Practices at SMK Negeri 2 Lubuklinggau. This research is an evaluation research with CIPP model. The methodology used is a quantitative methodology with the research subjects of students, prakerin supervisors, heads of working working groups and DUDI supervisors. Data collection techniques are observation, interviews, questionnaires (questionnaire) and documentation. Based on the results of data analysis, it was found that the evaluation of the prakerin implementation to increase labor absorption at SMK Negeri 2 Lubuklinggau was included in the criteria for both the context, input, process and product components but needed some improvements so that the absorption of labor in SMK Negeri 2 Lubuklinggau became optimal, namely renewal MoU with DUDI, alignment of curriculum or materials, material for providing higher quality prakerin and clear monitoring items. Improvements are needed in maximizing the relationship between schools and DUDI for the implementation of an aligned curriculum.